Phycoremediation of crude oil-contaminated water: Current microbial remediation protocol and effect on the ecosystem: A review (Journal of Pure and Applied Sciences (Science Forum), 2026)
Owing to the extensive use of petroleum hydrocarbons in the modern world, petrochemical derivatives have become one of the major environmental pollutants with ensuing environmental devastation. Pollution of aquatic environments by hydrocarbon via numerous anthropogenic and natural sources has become even more worrisome. The detrimental effects of this pollution on the aquatic micro and macroorganisms, including fishes, birds, and mammals, have been thoroughly documented. The associated health impacts of crude oil pollution on humans and the environment have resulted in the current microbial remediation protocol to alleviate the effect on the ecosystem. The physicochemical protocols of cleaning the aquatic environments of hydrocarbon pollutants have been found deficient because of the high cost and the need for high-tech equipment and expertise. The ability of diverse microorganisms to degrade hydrocarbon pollutants as sources of carbon has been well studied for over three decades. These studies have focused mostly on bacteria. The bacterial-based crude oil remediation protocol is an effective means of remediating crude oil-polluted environments. It is environmentally friendly and cost-effective. It is even more effective when in collaboration with different species of bacteria (consortium) or when in association with plants (rhizodegradation). However, bacterial-based metabolism of organic pollutants, like crude oil, comes with severe reduction in dissolved oxygen, giving rise to longer time for microbial adaptation to the pollutants and the actual degradation, thus raising questions on the application of bacterial-based remediation protocols. Studies on the hydrocarbon metabolism by algae are already available with some details on the oxygenic metabolic pathways. The present review, therefore, highlights the potentials/advantages of algae in crude oil remediation. In addition to algae’s direct involvement in the breakdown of hydrocarbon pollutants, it provides an enabling environment, like the copious supply of oxygen, for indigenous aerobic microbes equally involved in the remediation.